From Slave to Statesman : The Life of Educator, Editor, and Civil Rights Activist Willis M. Carter of Virginia - Heinrich, Robert, 1979-; Harding, Deborah (Book collections on Project MUSE., 2016)
In the 1980s, Willis McGlascoe Carter's handwritten memoir turned up unexpectedly in the hands of a midwestern antiques dealer. Its twenty-two pages told a fascinating story of a man born into slavery in Virginia who, at the onset of freedom, gained an education, became a teacher, started a family, and edited a newspaper. Even his life as a slave seemed exceptional: he described how his owners treated him and his family with respect, and he learned to read and write. Tucked into its back pages, the memoir included a handwritten tribute to Carter, written by his fellow teachers upon his death. Robert Heinrich and Deborah Harding's From Slave to Statesman tells the extraordinary story of Willis M. Carter's life. Using Carter's brief memoir--one of the few extant narratives penned by a former slave--as a starting point, Heinrich and Harding fill in the abundant gaps in his life, providing unique insight into many of the most important events and transformations in this period of southern history. -- Amazon.com.